Сварка и соединение — ключевые технологии третьего тысячелетия - Дилтай, У. (Автоматическая сварка, 2008)
Welding of advanced and modern materials and joining of material combinations create new demands for the welding and joining technologies. During the last ten years the new processes and process variations have been developed, particularly in the fields of arc and beam welding, with the aim to increase the economic efficiency, to reduce the energy input and to assure the quality of the welded joints. The socalled «cold joining technologies» became challenging. The work presents an outline of recent advancements of the welding and joining technologies, and specifies their technical and economical potentials.